'No-blame' redress scheme : a public consultation on draft proposals for a 'no-blame' redress scheme in Scotland for harm resulting from clinical treatment.: a public consultation on draft proposals for a 'no-blame' redress scheme in Scotland for harm resulting from clinical treatment. (2016) - Unknown
No abstract available